What is the best approach to managing a depressed patient who has not responded to a selective serotonin reuptake inhibitor (SSRI)?. Issue 4 (April 2017) - Gebauer, Sarah; Brieler, Jay
Abstract : EVIDENCE‐BASED ANSWER : Augmentation with a second‐generation atypical antipsychotic, lithium, or thyroid hormone increases response rates in depression resistant to monotherapy with an SSRI (SOR: A, meta‐analysis of RCTs). Switching to venlafaxine improves remission rates compared with switching to another SSRI (SOR: A, meta‐analysis of RCTs). Adding cognitive behavioral therapy (CBT) to usual treatment including antidepressants increases response and remission rates of treatment‐resistant depression compared with usual treatment alone (SOR: B, RCT).